Hybrid Molecular Imaging in Differentiated Thyroid Carcinoma - Schmidt, Daniela; Kuwert, Torsten (Frontiers of Hormone Research, 2016)
Radioactive isotopes of radioiodine are frequently used in differentiated thyroid carcinoma (DTC) both for diagnosis and therapy. Their accumulation in thyroid cancer tissue is dependent on the expression and activity of the sodium-iodide symporter (NIS). Scintigraphic imaging using either planar or single-photon emission computed tomography (SPECT) cameras allows the visualization of their distribution within the human body. Due to only a poor visualization of morphology by these techniques, their diagnostic accuracy is, however, limited. This limitation is overcome when hybrid systems integrating a SPECT camera with an X-ray CT scanner are used. Roughly one third of patients with diagnostically unclear foci of radioiodine accumulation will benefit from the use of SPECT/CT, also in terms of therapeutic management. SPECT/CT has, therefore, become the gold standard of nuclear imaging in DTC. NIS expression may be absent in DTC. In this case, the glucose transporters are usually upregulated. Therefore, PET/CT using 18F-deoxyglucose can be used to diagnose and localize tumor recurrence as a prerequisite to, in particular, surgical intervention.
EVALuna2:13862